Т.ҚАЙЫПБЕРГЕНОВ ПОВЕСТЛЕРИНДЕ КӨРКЕМЛЕЎ ҚУРАЛЛАРЫНАН ПАЙДАЛАНЫЎ ШЕБЕРЛИГИ - Сарсенбаев, Қ.Ж. (FAN va JAMIYAT, 2023)
The article presents about the language of Tolepbergen Kayipbergenov's stories, the meaning and structure of the lexical units used in the composition of the poem is studied in detail.